2012
DOI: 10.1128/jvi.01704-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of the SP2 Domain and Its Proteolytic Cleavage in HIV-1 Structural Maturation and Infectivity

Abstract: b HIV-1 buds as an immature, noninfectious virion. Proteolysis of its main structural component, Gag, is required for morphological maturation and infectivity and leads to release of four functional domains and the spacer peptides SP1 and SP2. The Nterminal cleavages of Gag and the separation of SP1 from CA are all essential for viral infectivity, while the roles of the two Cterminal cleavages and the role of SP2, separating the NC and p6 domains, are less well defined. We have analyzed HIV-1 variants with def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 50 publications
(67 reference statements)
7
61
0
Order By: Relevance
“…Inhibition of PR activity and premature processing due to enhanced activation of the enzyme are detrimental for virus replication (16). An ordered sequence of PR cleavage events has been deduced from in vitro analyses (17)(18)(19); accordingly, mutational analyses revealed that even partial blocking of processing at individual sites impairs viral infectivity, and an ordered series of cleavage events within Gag is important for formation of a mature viral core (20)(21)(22); reviewed in reference 23).…”
mentioning
confidence: 99%
“…Inhibition of PR activity and premature processing due to enhanced activation of the enzyme are detrimental for virus replication (16). An ordered sequence of PR cleavage events has been deduced from in vitro analyses (17)(18)(19); accordingly, mutational analyses revealed that even partial blocking of processing at individual sites impairs viral infectivity, and an ordered series of cleavage events within Gag is important for formation of a mature viral core (20)(21)(22); reviewed in reference 23).…”
mentioning
confidence: 99%
“…In conical capsids the genome is primarily located in the base of the cone, consistent with the experimental findings of Refs. 18,19,21,22 However, if the genome interacts attractively with the capsid wall, as is the case in the experiments of Ganser et al, 11 we find that with the same amount of genomic material and the same number of capsid proteins, the genome confinement free energy is slightly larger for a cone-shaped than that of a cylindrical capsid. This may explain why cones are less favorable than cylinders in in vitro HIV-1 experiments.…”
Section: Introductionmentioning
confidence: 63%
“…It has been suggested that while the viral protease cleaves the CA-NC link during maturation, incomplete cleaved links could be the reason why the RNA remains encapsulated in the mature capsid. 18,19 It is important to note that while the interaction between CA proteins is the driving force for Gag assembly in both the mature and immature hexagonal lattices, the free energy associated with the CA-CA interaction is thought to be weak, and the free energy of the CA-CA interaction in conical and cylindrical capsids has not yet been determined experimentally. To this end, in this paper, we only focus on the contribution of genome confinement free energy, assuming that the free energies due to CA-CA interaction between cylindrical and conical capsids are not considerable as they both appear in the in vitro studies in which no genome was present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations